Pengaruh Dan Peluang Usaha Terhadap Kesiapan Mahasiswa Untuk Menjadi Wirausaha - Erlina Ali Marpaung; Ella Fiana br Sitohang; Farah Dilla; Hasyim Hasyim (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The aim of this research aims to investigate the impact of factors that influence students' readiness to undertake an entrepreneurial career in an academic environment. These factors include education, motivation, practical experience, and social support from universities. In addition, this research also identifies relevant business opportunities that can support students in their entrepreneurial preparation. The type of research used in this research is qualitative research with descriptive methods. The descriptive method is considered suitable for explaining the influence and business opportunities on students' readiness to become entrepreneurs. The data in this research report was obtained in accordance with books, journals, articles, theses, the internet and so on related to the research topic. The results of this research provide valuable insight into how universities can more effectively prepare students to become successful entrepreneurs. The conclusion is that students have great potential to start their own businesses as long as they have innovative ideas, relevant skills, and access to the necessary resources. Keywords: Influence, Business Opportunities, Student Preparation, Entrepreneurship, Entrepreneurship Education, Motivation, Social Support, Academic Environment, Higher Education.